Health effects of climate change - Are they sufficiently addressed in pediatric settings in Germany to meet parents' needs? - Stephan Bose-O'Reilly; Maximilian Edlinger; Lena Lagally; Hannah Lehmann; Thomas Lob-Corzilius; Michael Schneider; Julia Schorlemmer; Peter van den Hazel; Julia Schoierer (Elsevier, 2022)
Children today are particularly vulnerable to direct and indirect health effects of climate change. Exposure to health hazards related to climate change will increase in the future. These health impacts increasingly pose additional challenges for the health care system, both in curative treatment and in preventive care. This paper therefore examines whether health care facilities for children and adolescents ("pediatric settings") in Germany are adequately preparing for the impact of climate change on children's health. For this purpose, we combine the results of two studies that investigated the relevance assessment of climate change-related health effects on children's health and the level of information on this topic among pediatricians (n = 408) and parents (n = 292). In addition, a narrative literature review was conducted. We have found that parents' need for information on this topic is currently not being met by pediatricians, as the topics of climate change and health are inadequately addressed in pediatric settings in Germany. Thus, there is a gap between the demand for information and the lack of supply that needs to be closed. To close the gap between parents' need for information on the impact of climate change on children's health and pediatricians' insufficient provision of information, more training materials, more trained staff and more climate change and health information resources are needed in pediatric settings. In order to provide all parents with evidence-based knowledge, the communication of the complex health effects should be readily accessible and target group-oriented.